On the Efficiency of Job Search with Social Networks - Pierre Cahuc; François Fontaine (Institute for the Study of Labor (IZA), 2002)
This paper provides a simple matching model in which unemployed workers and employers can be matched together through social networks and through more efficient, but also more costly, methods. In this framework, decentralized decisions to utilize social networks in the job search process can be inefficient and give rise to multiple equilibria for some parameters values. More precisely, in a decentralized equilibrium, social networks can be over-utilized, with respect to an efficient allocation, in some circumstances and under-utilized in others. Moreover, the existence of different job search methods can give rise to a higher job search intensity than the efficient one. This is in sharp contrast with the standard result, derived in matching models, according to which search intensity is always too low if not efficient. Eventually, in the presence of different job search methods, conditional unemployment benefits hikes can improve welfare when individuals are risk neutral.
Keywords: J68; J64; E24; 330; social networks; unemployment; job search; Arbeitsuche; Soziales Netzwerk; Theorie